APPLICATION OF HUMAN RESOURCE MANAGEMENT FREE OF ISLAMIC VALUES - Nazifah Husainah; Maswanto Maswanto; M. Yusuf; Hapzah Shalsa Sabila (PENANOMICS: International Journal of Economics, 2022)
The purpose of this study is to find out how the application of MSDM to Islamic banks, whether it is in accordance with Islamic values, by looking at the management practices carried out by Islamic banks. This research uses a qualitative method where data collection is carried out with interviews and observations in more depth during a certain period so as to be able to explore and get further information about the application of MSDM based on Islamic values. The object of this study is a bank engaged in a sharia system. Then the sample in this study is an employee at a Sharia bank who has served for more than 1 year and is a permanent employee. The results obtained state that in general, Islamic values are still considered and applied in MSDM practice in Islamic banks. The Islamic aspect is demonstrated by including some criteria, tests, or materials in some management practices. Then the spirituality side is also seen from the participation of employees in several religious activities held, this reflects the Islamic side of a person.